Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A = 1/1*2 + 1/2*3 + 1/3*4 + ... + 1/99*100
A = 1 - 1/2 + 1/2 - 1/3 + 1/3 - 1/4 + ... + 1/99 - 1/100
A = 1 - 1/100
A = 99/100
B = 5/1*4 + 5/4*7 + .... + 5/100*103
B = 5/3*(3/1*4 + 3/4*7 + ... + 3/100*103)
B = 5/3*(1 -1/4 + 1/4 - 1/7 + ... + 1/100 - 1/103)
B = 5/3*(1 - 1/103)
B = 5/3* 102/103
a) 3A=1.2.3 + 2.3.3 + 3.4.3 +... + n.(n+1).3
=1.2.(3-0) + 2.3.(4-1) + ... + n.(n+1).[(n+2)-(n-1)]
=[1.2.3+ 2.3.4 + ...+ (n-1).n.(n+1)+ n.(n+1)(n+2)] - [0.1.2+ 1.2.3 +...+(n-1).n.(n+1)]
=n.(n+1).(n+2)
=>S=[n.(n+1).(n+2)] : 3
a) \(\frac{1}{n}-\frac{1}{n+a}=\frac{n+a-n}{n\left(n+a\right)}=\frac{a}{n\left(n+a\right)}\)
b) \(\frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{2008.2009}=1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+...+\frac{1}{2008}-\frac{1}{2009}=1-\frac{1}{2009}=\frac{2008}{2009}\)
c) \(\frac{3}{1.4}+\frac{3}{4.7}+...+\frac{3}{94.97}=1-\frac{1}{4}+\frac{1}{4}-\frac{1}{7}+...+\frac{1}{94}-\frac{1}{97}=1-\frac{1}{97}=\frac{96}{97}\)
a, Ta có: \(\dfrac{1}{n}.\dfrac{1}{n+4}=\dfrac{1}{n.\left(n+4\right)}=\dfrac{1}{4}.\dfrac{4}{n.\left(n+1\right)}=\dfrac{1}{4}.\left(\dfrac{1}{n}-\dfrac{1}{n+4}\right)\)
Vậy \(\dfrac{1}{n}.\dfrac{1}{n+1}=\dfrac{1}{4}.\left(\dfrac{1}{n}-\dfrac{1}{n+4}\right)\)
b, \(A=\dfrac{4}{3}.\dfrac{4}{7}+\dfrac{4}{7}.\dfrac{4}{11}+...+\dfrac{4}{95}.\dfrac{4}{99}=4.\left(\dfrac{4}{3.7}+\dfrac{4}{7.11}+...+\dfrac{4}{95.99}\right)\)
\(=4.\left(\dfrac{1}{3}-\dfrac{1}{7}+\dfrac{1}{7}-\dfrac{1}{11}+...+\dfrac{1}{95}-\dfrac{1}{99}\right)\)
\(=4.\left(\dfrac{1}{3}-\dfrac{1}{99}\right)=4.\dfrac{32}{99}=\dfrac{128}{99}\)
Vậy \(A=\dfrac{128}{99}\)
a) \(N=\frac{1}{4^2}+\frac{1}{6^2}+\frac{1}{8^2}+...+\frac{1}{\left(2n\right)^2}\)
\(N=\frac{1}{2^2}.\left(\frac{1}{2^2}+\frac{1}{3^2}+\frac{1}{4^2}+...+\frac{1}{n^2}\right)\)
Đặt A = \(\frac{1}{2^2}+\frac{1}{3^2}+\frac{1}{4^2}+...+\frac{1}{n^2}\)
A < \(\frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{\left(n-1\right).n}\)
\(=1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{n-1}-\frac{1}{n}\)
\(=1-\frac{1}{n}< 1\)( vì n \(\ge\)2 )
\(\Rightarrow N=\frac{1}{2^2}.\left(\frac{1}{2^2}+\frac{1}{3^2}+\frac{1}{4^2}+...+\frac{1}{n^2}\right)< \frac{1}{2^2}.1=\frac{1}{4}\)
Vậy \(N< \frac{1}{4}\)
b) \(P=\frac{2!}{3!}+\frac{2!}{4!}+\frac{2!}{5!}+...+\frac{2!}{n!}\)
\(P=2!\left(\frac{1}{3!}+\frac{1}{4!}+\frac{1}{5!}+...+\frac{1}{n!}\right)\)
\(P< 2.\left(\frac{1}{2.3}+\frac{1}{3.4}+\frac{1}{4.5}+...+\frac{1}{\left(n-1\right).n}\right)\)
\(P< 2.\left(\frac{1}{2}-\frac{1}{n}\right)=1-\frac{2}{n}< 1\)
Vậy \(P< 1\)
4A = 4.[1.2.3 + 2.3.4 + 3.4.5 + … + (n – 1).n.(n + 1)]
4A = 1.2.3.4 + 2.3.4.4 + 3.4.5.4 + … + (n – 1).n.(n + 1).4
4A = 1.2.3.4 + 2.3.4.(5 – 1) + 3.4.5.(6 – 2) + … + (n – 1).n.(n + 1).[(n + 2) – (n – 2)]
4A = 1.2.3.4 + 2.3.4.5 – 1.2.3.4 + 3.4.5.6 – 2.3.4.5 + … + (n – 1).n(n + 1).(n + 2) – (n – 2).(n – 1).n.(n + 1)
4A = (n – 1).n(n + 1).(n + 2)
A = (n – 1).n(n + 1).(n + 2) : 4.
a) n + 4 chia hết cho n - 1
⇒ n - 1 + 5 chia hết cho n - 1
⇒ 5 chia hết cho n - 1
⇒ n - 1 ∈ Ư(5)
⇒ n - 1 ∈ {1; -1; 5; -5}
⇒ n ∈ {2; 0; 6; -4}
b) n2 + 2n - 3 chia hết cho n + 1
⇒ n2 + n + n - 3 chia hết cho n + 1
⇒ n(n + 1) + (n - 3) chia hết cho n + 1
⇒ n - 3 chia hết cho n + 1
⇒ n + 1 - 4 chia hết cho n + 1
⇒ 4 chia hết cho n + 1
⇒ n + 1 ∈ Ư(4) = {1; -1; 2; -2; 4; -4}
⇒ n ∈ {0; -2; 1; -3; 3; -5}
a. ( n + 4 ) ⋮ ( n - 1 )
⇒ ( n - 1 ) + 5 ⋮ ( n - 1 )
Do ( n - 1 ) ⋮ ( n - 1 )
nên 5 ⋮ ( n - 1 )
⇒ ( n - 1 ) \(\in\) Ư(5)
( n - 1 ) = { 1 ; - 1 ; 5 ; - 5 }
n = { 2 ; 0 ; 6 ; - 4 }